Frequency of respiratory symptoms among rice mill workers in Bangladesh: A cross‐sectional study - Shah A. R. A. Choudhury; Abu Rayhan; Shamim Ahmed; Rajashish Chakrabortty; Mohammed A. Rahman; Abdullah A. Masud; Susanta K. Paul; Ahmed Sami Al Hasan (Health Science Reports, 2023)
Abstract Background and Aims Rice mill workers are frequently exposed to rice dust specks containing bacteria, endotoxins, spores, and chemicals in workplaces. Consequently, they develop diverse respiratory symptoms that lead to increased disability and social burden. The present study was conducted to observe the frequency of respiratory symptoms among rice mill workers in Bangladesh. Methods This cross‐sectional study was conducted at different rice mills in Rangpur district of Bangladesh. Three hundred and forty‐six rice mill workers, both male and female of 18 years and above, with a job experience of at least 3 years, were selected as study subjects. An equal number of people who had never worked at rice mills were selected from the nearby locality as the nonexposed group. Enquiries were made regarding respiratory symptoms with the help of a preformed questionnaire which contained sociodemographic characteristics, occupational history, potential confounding factors, and physical parameters. A respiratory dust sampler was used to measure workplace dust concentration. Results The presence of one or more respiratory symptoms was significantly higher among rice mill workers than in the nonexposed group (52.3% vs. 17.6%). Rice mill workers who worked for more than 10 h and had a working experience of more than 15 years had a higher frequency of respiratory symptoms (41.3% and 39.8%, respectively). Rice mill workers with body mass index (BMI) <18.5 also exhibited more respiratory symptoms (25.4%). All working sections had a higher‐than‐average dust concentration level, with the milling section being the dustiest (PM 2.5 492.1 µg/m3). Conclusion This study showed an increased frequency of respiratory symptoms among rice mill workers of Bangladesh. Longer working experience and working hours, low BMI and high dust concentration levels were strongly associated with that increase in frequency.